Design and Development of a Command and Control Unit (CCU) on an Unmanned Surface Vehicle (USV) for Water Observation - Setyawan Ajie Sukarno; Hendy Rudiansyah; Hasan Tirta Maulana; Muhammad Kadir; Fajar Setio Adi (International Journal of Marine Engineering Innovation and Research, 2025)
The development of a data acquisition and control system based on modern technologies plays a crucial role in supporting aquatic environmental exploration using Unmanned Surface Vehicles (USVs). This project aims to design and implement a command-and-control unit capable of integrating water survey instruments with microcontroller-based sensors, targeting the real-time display of depth data, GPS location, and graphical visualization on an Smartphone application. The system employs the ESP32 module as the bridge between USV sensors—such as a single-beam echo sounder for depth measurement and a GPS module—and the user application. Wi-Fi connectivity is utilized for fast and efficient data transmission between the USV and the mobile interface. In this project, the Arduino IoT Cloud platform is adopted to simplify the integration of real-time data into the user interface, eliminating the need to develop an application from scratch. The system is designed to be cost-effective, portable, and user-friendly. This project is expected to demonstrate the system’s capability to process sensor-acquired data, control the USV’s movement direction, and display the results in numerical and graphical formats on the user's Android device in real time